Pengaruh Pemberian Reward (Bintang) terhadap Minat Belajar Peserta Didik di MAN 1 Pandeglang - Septi Lutfitawati; Amelia Putri; Sundawati Tisnasari; Azka Rizkia MS Salsabila (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The purpose of this study is to determine the effect of giving rewards in the form of star stamps on students' interest in learning. Students' interest in learning is very important in a learning process, because students will easily absorb learning materials by having a high interest in learning. Students' interest in learning can be aroused by the efforts of teachers in the learning process, one of which is with high creativity so that students are more interested in learning. Background Giving star rewards to students is a simple and fun form of appreciation. This type of research is qualitative research with descriptive explanations. Data collection in this study was through a questionnaire filling sheet in the form of a google form which was distributed through the class WhatsApp group. The results of the study were obtained in the form of data to be analyzed, then it can be concluded that the provision of rewards in the form of stars has an influence on increasing students' interest in learning. This has been proven by several answers from questionnaires filled out by students at MAN 1 Pandeglang.